PENGARUH MEDIA EDUKASI E-BOOKLET TERHADAP TINGKAT PERILAKU TENAGA TEKNIS KEFARMASIAN PADA PENGGALIAN INFORMASI SWAMEDIKASI COMMON COLD - Septi Muharni; Fadila Toha; Fina Aryani; Husnawati (Jurnal Penelitian Farmasi Indonesia, 2022)
Self-medication service is a high service practice carried out by pharmaceutical technical personnel, one of which is the common cold self-medication service. This demands a fairly high TTK role, one of which is in information research. The purpose of this study was to see the effect of providing educational media for TTK level e-booklets on common cold self-medication information. This research is quasi-experimental research: non-equivalent control group design using non-probability sampling method with purposive sampling technique. The sample in this study was 100 TTK who were registered with the Regional Board of the Indonesian Pharmacists Association of Riau Province and worked in pharmacies. The data were analyzed by marginal homogeneity test with significant results in the provision of educational media e-booklets on the level of TTK behavior in the treatment group during pre-test and post-test with p value = 0,011 (p <0.05). Based on the results of this study, it is said that presenting e-booklet educational media can increase TTK in Riau Province on the behavior of self-medication information on common cold.